Transforming Access and Utilization of Skilled Delivery Services in Pastoral Districts of South Omo Zone, Ethiopia - Mrs. Roman Tesfaye Abneh (My University, 2025)
This article presents empirical evidence on the impact of the Hailemariam & Roman Foundation (HRF)’s support in transforming Reproductive, Maternal, Newborn, and Child Health (RMNCH) interventions jointly implemented with local government and communities between 2021 and 2024 in the Hamer and Bena Tsemay woredas (districts) of South Omo Zone, Ethiopia. The initiative achieved a 91 % increase over 2 and ½ years in skilled birth attendance in Hamer Woreda (from 34% to 65%) and an 11.6% increase in Bena Tsemay (from 86% to 96%) over the same period, surpassing Ethiopia’s national target of 90% (FMoH, 2020) in Bena Tsemay. Over 175 health professionals, 20 health managers and leaders, and 22 community leaders were trained, while 71 Traditional Birth Attendants (TBAs) were trained to serve as liaisons and promoters of giving birth at health facilities—a strategy aligned with WHO recommendations for engaging informal providers to expand maternal health service coverage (WHO, 2015). Additionally, antenatal care (ANC) coverage increased, with over 80% of women attending at least one ANC visit, and 60% completing four or more—a significant improvement from baseline levels. Postnatal care (PNC) within 48 hours rose from under 20% to over 50%, and ambulance referrals quadrupled, enhancing emergency obstetric response. The findings demonstrate the effectiveness of combining health system strengthening, community-based interventions, strategic advocacy, and culturally tailored solutions to significantly improve maternal and neonatal health outcomes in underserved and remote areas, offering a compelling case for scaling up context-specific RMNCH strategies across pastoralist settings within the country and sub-Saharan Africa.